Evaluasi Sistem Pengelolaan KKN: Studi Perspektif Mahasiswa Magang - Nurziah Nurziah; Reza Luqman Hakim; Ince Dian Afnita; Irma Suriyani (JURNAL RISET MANAJEMEN (JURMA), 2026)
This study aims to evaluate the management system of the Community Service Program (Kuliah Kerja Nyata/KKN) implemented by the Institute for Research and Community Service (LPPM) from the perspective of student participants as internal actors. KKN is a form of community engagement program that requires an effective management system to ensure its objectives are achieved optimally. This research employs a qualitative approach with a descriptive-exploratory design. Data were collected through Focus Group Discussions (FGDs), participant observation, and document analysis, then analyzed using the interactive model proposed by Miles et al. The findings indicate that the KKN management system still faces several challenges, including administrative irregularities, weak coordination and communication among stakeholders, limited information system support, and insufficient technical readiness during implementation. In addition, students provide critical reflections on their roles and experiences throughout the program. The problems identified are not only caused by institutional factors but also by interactions among actors within the KKN implementation system. This study highlights the importance of strengthening system integration, improving the quality of coordination among related parties, and developing digital-based information systems. These efforts are expected to enhance the effectiveness of KKN implementation and improve overall program governance in a sustainable manner.